2016
DOI: 10.1111/jan.13095
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a comprehensive reminder system in the secondary prevention of hypertensive ischaemic stroke: randomized controlled trial protocol

Abstract: Although many efforts to improve secondary stroke prevention have been undertaken, research indicates that improvements remain possible and warranted. This research protocol based on the Health Belief Model will improve our understanding of stroke education and transitional care needed in China and with the world-wide target population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…One study [ 35 ] had three arms (two intervention arms and an attention matched control arm that performed an upper limb training programme). The remaining eight studies [ 31 34 , 36 39 ] had two arms (intervention versus usual care/attention matched control).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study [ 35 ] had three arms (two intervention arms and an attention matched control arm that performed an upper limb training programme). The remaining eight studies [ 31 34 , 36 39 ] had two arms (intervention versus usual care/attention matched control).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies included short- (3-months [ 32 34 , 36 , 38 , 39 ]) and medium-term follow-up periods (6-months [ 31 34 , 36 , 37 ]), with only two studies conducting long-term (12 months [ 31 , 35 ]) follow-up assessments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that the changes in mRS score of both control group (change = −0.31, p = .004) and intervention group (change = −0.59, p < .001) were statistically significant at 6‐month after discharge. This may be because the patients with physical disability would seek functional rehabilitation actively (Wan, 2017). The main factors influencing functional rehabilitation of stroke patients should be further explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a Comprehensive Reminder System based on Health Belief Model (CRS‐HBM) was established (Wan, You, et al, 2016) and the 3‐month results showed that the CRS‐HBM improved health behaviour and BP control and decreased the severity of disability in hypertensive ischemic stroke patients (Wan, Zhang, You, Ruan, & Chen, 2018). Health behaviours and effective BP control were very important for secondary prevention of stroke.…”
Section: Introductionmentioning
confidence: 99%